The Impact of Islamic Financial Development, GDP, and Population on Environmental Quality in Indonesia - Nengsih, Titin Agustin; Abduh, Muhamad; Ladini, Urwawuska; mubarak, Fadhlul (International Journal of Energy Economics and Policy, 2023)
Environmental problems are becoming an issue along with the issue of global warming whose impacts are increasingly being felt. Cases of environmental destruction in Indonesia are increasing, so several directions of government policies have started toward sustainable development goals (SDGs). The situation has challenged Islamic finance, an alternative financial system that is said to be the answer to the current toxic financial system, to prove itself to support the environment quality. This research aims to determine the impact of Islamic financial development, Gross Domestic Product (GDP), and population on the environmental quality in Indonesia using data spanning from 2016 to 2020. The results show that GDP significantly impacts the environmental quality of almost all major islands in Indonesia. Overall, in the territory of Indonesia Islamic financial development had a significantly negative effect at a significant level of 10% on environmental quality.